Willingness to receive intravenous buprenorphine treatment in opioid-dependent people refractory to oral opioid maintenance treatment: results from a community-based survey in France - Perrine Roux; Daniela Rojas Castro; Khadim Ndiaye; Laélia Briand Madrid; Virginie Laporte; Marion Mora; Gwenaelle Maradan; Stéphane Morel; Bruno Spire; Patrizia Carrieri (BMC, 2017)
Abstract Background Injectable opioids are an interesting option for people who inject drugs (PWID) that do not respond to oral Opioid Maintenance Treatment (OMT). To date, intravenous (IV) buprenorphine - a safer drug than full-opioid agonists in terms of overdose risk - has never been tested in a clinical trial on opioid dependence. We designed a survey to better understand the profile of PWID eligible for IV buprenorphine, and their willingness to receive it. Methods This cross-sectional community-based national survey was conducted through face-to-face interviews (in low-threshold and addiction care services) and online questionnaires (on https://psychoactif.org and other websites). Among the 557 participants, we selected those who were eligible for IV buprenorphine treatment (history of oral OMT, regular opioid injection) (n = 371). We used regression models to study factors associated with willingness to receive IV buprenorphine treatment among those with data on willingness (n = 353). In those who were willing (n = 294), we subsequently studied their willingness to receive daily supervised IV buprenorphine treatment. Results Among the selected 353 participants, 59% mainly injected buprenorphine, 15% heroin, 16% morphine sulfate and 10% other opioids. Eighty-three percent of the sample reported willingness to receive IV buprenorphine treatment. Factors associated with willingness were: more than 5 injection-related complications, regular buprenorphine injection, no lifetime overdose, and completion of the questionnaire online. Factors associated with unwillingness to receive daily supervised treatment were younger age (OR[IC95%]=1.04[1.01; 1.07]) and stable housing (OR[IC95%]=0.61[0.37;1.01]) while regular heroin injectors were more willing to receive daily supervision (OR[IC95%]=2.94 [1.42; 6.10]). Conclusions PWID were very willing to receive intravenous buprenorphine as a treatment, especially those with multiple injection-related complications. In addition, our findings show that IV buprenorphine may be less acceptable to PWID who inject morphine sulfate. Young PWID and those with stable housing were unwilling to receive IV buprenorphine if daily supervision were required. This preliminary study provides useful information for the development of a clinical trial on IV buprenorphine treatment.